How the Workload and Outcome of Imaging Examinations Changed During the COVID-19 Pandemic Lockdown: How the Workload and Outcome of Imaging Examinations Changed During the COVID-19 Pandemic Lockdown - Vingiani, Vincenzo; Abadia, Andres F.; Posa, Alessandro; Corvino, Antonio; Pasqualetto, Luigi; Presidente, Alfonso; Losco, Matteo; Gray, Hunter N; Schoepf, U. Joseph (Acta Biomedica Atenei Parmensis, 2020)
Background: On March 9th, 2020, the Italian government decided to go into lockdown due to the COVID-19 pandemic, which led to changes in the workflow of radiological examinations. Aims: Aim of the study is to illustrate how the workload and outcome of radiological exams changed in a community hospital during the pandemic. Methods and Material: The exams performed in the radiology department from March 9th to March 29th, 2020 were retrospectively reviewed and compared to the exams conducted during the same time-period in 2019. Only exams coming from the emergency department (ED) were included. Two radiologists defined the cases as positive or negative findings, based on independent blind readings of the imaging studies. Categorical measurements are presented as frequency and percentages, and p-values are calculated using the Chi-squared test. Results and Conclusions: There was a significant reduction in the amount of exams performed in 2020: there were 143 (93|65% male, 60.7±21.5 years) patients who underwent radiological examinations from the ED vs. 485 (255|53% male, 51.2±24.8 years) in 2019. Furthermore, the total number of ED exams dropped from 699 (2019) to 215 (2020). However, the percentage of patients with a positive result was significantly higher in 2020 (69|48%) compared to 2019 (151|31%) (p<.001). The reduction of emergency radiological examinations might be a result of the movement restrictions enforced during the lockdown, and possible fear of the hospital as a contagious place. This translated to a relative increase of positive cases as only patients with very serious conditions were accessing the ED.